2004
DOI: 10.1182/blood-2003-03-0762
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of removal of human cytomegalovirus from blood components by leukocyte depletion filters using real-time quantitative PCR

Abstract: To assess removal of cytomegalovirus (CMV) by leukocyte depletion (LD) filters, we developed a spiking model of latent virus using peripheral blood mononuclear cells (PBMCs) infected by coculture with CMV-infected human fibroblasts. Infected PBMCs were purified by dual magnetic column selection and then spiked into whole blood units or buffy coat pools prior to LD by filtration. CMV load and fibroblast contamination were assessed using quantitative CMV DNA real-time PCR and quantitative reverse transcriptase-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
(23 reference statements)
1
23
0
4
Order By: Relevance
“…Daraus folgt auch, dass die Infektion von der Mehrheit der seropositiven Spender nicht übertragen wird [11,64,112]. Durch HCMV-seronegative zelluläre Blutkomponenten wurde das Risiko einer HCMV-Infektion bei der Verabreichung nicht leukozytendepletierter Blutkomponenten verringert [113,114]. Die generelle Verwendung von leukozytendepletierten Blutkomponenten hat das Risiko ebenfalls gesenkt.…”
Section: üBertragbarkeitunclassified
See 1 more Smart Citation
“…Daraus folgt auch, dass die Infektion von der Mehrheit der seropositiven Spender nicht übertragen wird [11,64,112]. Durch HCMV-seronegative zelluläre Blutkomponenten wurde das Risiko einer HCMV-Infektion bei der Verabreichung nicht leukozytendepletierter Blutkomponenten verringert [113,114]. Die generelle Verwendung von leukozytendepletierten Blutkomponenten hat das Risiko ebenfalls gesenkt.…”
Section: üBertragbarkeitunclassified
“…Experimentell wurde in leukozytendepletierten Blutkomponenten eine Reduktion der zellgebundenen HCMV-DNA um ca. 3 log 10 -Stufen gezeigt [114,115]. Die minimale infektiö-se Dosis für eine HCMV-Infektion beim Menschen konnte bisher nicht definiert werden.…”
Section: üBertragbarkeitunclassified
“…The general use of leucocytedepleted blood components has also reduced this risk. Spiking experiments have shown a reduction in leucocyte-depleted blood components of about 3 log levels with regard to cellular HCMV DNA [84,85].…”
Section: Transmissibilitymentioning
confidence: 99%
“…It can be concluded that infection is not transmitted from the majority of seropositive donors [8,48,82]. As long as non-leucocytereduced blood components were administered, the risk of HCMV infection was reduced by HCMV-seronegative cellular blood components [83,84]. The general use of leucocytedepleted blood components has also reduced this risk.…”
Section: Transmissibilitymentioning
confidence: 99%
“…Other pathogens, for example Trypanosoma cruzi, may be highly prevalent in certain immigrant populations, and there may be no routine tests in place to identify infected donors [6]. Additional highly prevalent latent pathogens such as cytomegalovirus (CMV) may not be completely eliminated by current methods [7][8][9]. The risk of a transfusion-transmitted bacterial contamination is even more compelling.…”
mentioning
confidence: 99%